Self-assembly of trithia-9-crown-3 and octathia-24-crown-8 on Au(111) surfaces. Issue 85 (30th August 2016) - Liu, Xiao-Ping; Deng, Ke; Wei, Qian; Liang, Ming-hui; Zhang, Zhan-Jun; Jiang, Peng
Abstract : Scanning tunneling microscopy images of trithia-9-crown-3 and octathia-24-crown-8 self-assembled monolayers (SAMs) reveal completely different SAM structures for the two kinds of thiacrown molecules at liquid n -tetradecane/Au(111) interface. Abstract : We have investigated the formation of trithia-9-crown-3 (9S3) and octathia-24-crown-8 (24S8) self-assembled monolayers (SAMs) at liquid n -tetradecane/solid Au(111) interface using scanning tunneling microscopy (STM) at room temperature. STM images with a molecular resolution reveal completely different shape- and size-dependent SAM structures for the two kinds of thiacrown molecules. The experimental results demonstrate that 9S3 molecules lie flat, while 24S8 stand up on the Au(111) surfaces. Both of them form long-range ordered SAM structures. The unexpected standing conformations of 24S8 molecules on Au(111) provide a new opportunity for designing and forming shape- and size-controlled nanosized ordered SAM structures via strong chemical interactions between TCEs and metallic gold substrate as well as between TCEs and bio-macromolecules simultaneously for advanced sensors.